Optimization of Gamification Type Selection in Pop-Up Campaigns to Enhance Customer Engagement on E-Commerce Platform XYZ Using the Analytical Hierarchy Process Method - Kesy Apriansyah; Hakim, Dimara Kusuma; Feri Wibowo; Supriyono (Politeknik Piksi Ganesha Indonesia, 2025)
One of the key success factors in the e-commerce industry is the increase in consumer engagement. High engagement has been proven to drive sales growth and customer loyalty. To achieve this goal, the application of gamification in marketing campaigns has been shown to have a significant impact on customer engagement in e-commerce. This study aims to optimize the selection of gamification types in pop-up campaigns to enhance consumer engagement on the XYZ e-commerce platform. The selection of the right type of gamification is crucial, but it is often influenced by subjectivity in assessment. To that end, this research uses the Analytic Hierarchy Process (AHP) method, which integrates historical data as a reference in filling alternatives based on criteria to reduce the subjectivity of the AHP method in determining the most effective type of gamification based on the criteria of Click-Through Rate (CTR), Conversion Rate (CR), and Impression. The research results show that the Memory Card type of gamification is the most effective type with the potential to increase consumer engagement. This approach is expected to serve as a reference for e-commerce platforms in designing more effective and data-driven gamification strategies.